Proceedings of the 6th International Conference on Pervasive Computing Technologies for Healthcare 2012
DOI: 10.4108/icst.pervasivehealth.2012.248710
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Theory as a Framework For Interventions That Support Parents of NICU Infants

Abstract: Transitioning a Very Low Birth Weight (VLBW) premature infant from the Neonatal Intensive Care Unit (NICU) to home is a very stressful task for parents. Few studies examined the needs of parents of VLBW infants during the transition; moreover, even less is known about technology development strategies that aim to increase the parenting confidence. In this study, we used Bandura's self-efficacy theory as a framework to understand ways to develop successful interventions for parents of VLBW infants. The self-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous studies have found that interventions based on selfefficacy theory were feasible and effective in behavioral change. [16][17][18] Self-efficacy is the belief in one's capabilities to perform a task, giving motivation and ability to someone to achieve success. It is usually influenced through performance accomplishments; vicarious experience; verbal persuasion; and physiological and affective states.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that interventions based on selfefficacy theory were feasible and effective in behavioral change. [16][17][18] Self-efficacy is the belief in one's capabilities to perform a task, giving motivation and ability to someone to achieve success. It is usually influenced through performance accomplishments; vicarious experience; verbal persuasion; and physiological and affective states.…”
Section: Introductionmentioning
confidence: 99%
“…The Cambodian staff at SKMH expected a quality product, and it would not be inappropriate to state that patient care was dependent upon the quality and accuracy of deliverables provided to the SKMH staff. As Bandura's model calls for self-efficacy development through mastery experiences, vicarious experiences and social persuasion (Lee et al, 2012), this theory was useful in guiding the relationship between the faculty mentor and the members of the student team. The goal was for student team members to feel successful and build self-confidence through each phase of the project.…”
Section: Bandura's Social Cognitive Theorymentioning
confidence: 99%